Rick - Gino, Alex (Scholastic Inc., 2022)
Although Rick has never thought about his identity much, when he begins middle school, he attends the Rainbow Spectrum Club where he meets kids of all genders and identities, including a girl named Melissa. Rick wants to have his life all figured out like Melissa, so he begins a quest to find his place in the world, even if it means breaking some old friendships.